ETHNOGRAPHY OF REMOTE CUSTOM COMMUNITIES OF MURKIM TRIBES IN KEEROM REGENCY - PAPUA - Wenehen, Agustinus; Maryani, Agnes Eri (Sosiohumaniora, 2024)
This study takes a cultural theory approach to portraying and analysing the various socio-cultural institutions of the Murkim Tribe's Remote Custom Communities residents in Miliki Village, Keerom Regency. According to this theory, the Murkim Tribe is a social community with the ability to empower itself by utilising its various sociocultural institutions. The researcher used ethnographic methods to gain an understanding of the Murkim Tribe's perspective on their lives and world. Data were collected through in-depth interviews with traditional leaders as key informants using the snowball sampling technique, as well as through focus group discussions (FGDs) with representatives of the village government, customs, religion, youth and women, exploring their hopes, aspirations and observations. The results demonstrate that the Murkim Tribe maintains the following socio-cultural institutions: (1) the Kiminismi traditional house, which is used for celebrations and ceremonies; (2) the Petak exchange marriage system, which frequently leads to internal conflicts; (3) customary boundaries, which affect village government dualism; and (4) the Anokrum war chief, who plays a significant role in many areas of life. The results suggest developing, empowering and guiding Murkim Tribe residents in Milki Village using an in-situ model that considers limiting factors such as regional policies, a high-cost economy, disputes over customary land and issues with food security. The SWOT analysis (strengths, weaknesses, opportunities and threats) concludes that Milki Village is well-positioned to develop the Murkim communities. Therefore, collaborative planning and development efforts are essential to ensure that Murkim Tribe can break free from poverty and underdevelopment.